Prostacyclin, thromboxane and glomerular filtration rate are abnormal in sickle cell pregnancy - Obilade, Opeyemi Abayomi; Akanmu, Alani Suleimon; Broughton Pipkin, Fiona; Afolabi, Bosede Bukola (Public Library of Science, 2017)
BACKGROUND: Pregnancy increases the risk of morbidity and mortality in sickle cell disease. We previously showed pregnant women with sickle cell disease to have a relatively low plasma renin concentration in late pregnancy, associated with a lack of the expected plasma volume expansion. We hypothesized this to be due to increased systemic vascular resistance through an imbalance between the vasodilator prostacyclin and vasoconstrictor thromboxane, associated with decreased glomerular filtration rate (GFR). OBJECTIVE: To compare estimated prostacyclin, thromboxane and GFR in non-pregnant and pregnant women with hemoglobin SS (HbSS) and AA (HbAA). STUDY DESIGN: Four groups of 20 normotensive, nulliparous women were studied in Lagos, Nigeria: pregnant HbSS or HbAA women at 36-40 weeks gestation; non-pregnant HbSS and HbAA controls. We measured stable metabolites of prostacyclin and thromboxane A2 by enzyme-linked immunosorbent assay; GFR using the Cockcroft-Gault equation. Data analysis was by independent (Student's) t-test or Mann-Whitney U test for comparisons between any two groups of continuous variables, univariate ANOVA for multiple groups and Pearson's correlation coefficient for degree of association between variables. RESULTS: HbSS women had lower serum 6-keto-PGF1α concentrations than HbAA, whether pregnant or non-pregnant (P<0.001; P<0.004 respectively). Conversely, pregnant HbSS women had higher serum TxB2 (P<0.001); non-pregnant HbSS women had non-significantly higher TxB2 concentrations. The 6-keto-PGF1α:TxB2 ratio was markedly increased (pro-vasodilatory) in HbAA pregnancy (P<0.001) but reduced in HbSS pregnancy (P = 0.037). GFRs (mL/min) were higher in non-pregnant HbSS than HbAA (P<0.008) but only marginally raised in HbSS women in late pregnancy (P = 0.019) while markedly raised in HbAA pregnancy (P<0.001). CONCLUSION: The lower ratio of prostacyclin-thromboxane metabolites in HbSS pregnancy may indicate endothelial damage and an increased tendency to vasoconstriction and clotting. If confirmed by subsequent longitudinal studies, interventions to increase prostacyclin and reduce thromboxane, such as low dose aspirin, may be potentially useful in their management.